Predictors of COVID-19 vaccination intention among Iranian population: applying the theory of planned behavior - Barati, Majid; Bashirian, Saeed; Abdi, Jalal; Sadri, Mohadeseh; Afshari, Maryam; Taheri, Malihe; Khazaei, Salman; Rostami-Moez, Masomeh (GMS hygiene and infection control, 2022)
The present study was conducted to assess the determinants of the intention to receive the COVID-19 vaccination among the Iranian population. In this cross-sectional study, 1,056 individuals of the general population living in Hamadan County were studied from April to June 2021. Using a proportional stratified sampling method, subjects were selected from those covered by 34 comprehensive health service centers and health bases. Then, the subjects were selected by simple random sampling. Data were collected by sending a questionnaire link to eligible individuals, who completed it online. The questionnaire determined demographic data and constructs of the Theory of Planned Behavior. 1,056 subjects answered the study; women accounted for 57.9% of the respondents. According to the findings, the majority of respondents (79.5%) reported that they would strongly agree and agree to get vaccinated against COVID-19. Older age, male gender, occupation, underlying chronic disease, death of relatives and friends due to COVID-19, and history of influenza vaccinations were significantly related to the intention to get vaccinated against COVID-19 (P>0.05). Also, the intention was associated with increased scores in the attitude toward the behavior, subjective norm, and perceived behavioral control. Despite doubt about the details of the intention to receive COVID-19 vaccination, most subjects reported intending to be vaccinated against COVID-19, but the real rate of vaccination may be lower. Vaccination intention reflects overall vaccination attitudes, subjective norms, and perceived behavioral control.